KOMPRES HANGAT MEMPENGARUHI DERAJAT NYERI MENSTRUASI PADA SISWI KELAS X DI SMA NEGERI 2 PAMEKASAN - Makrifatul Amaliyah; R. Khairiyatul Afiyah (Universitas Nahdlatul Ulama Surabaya, 2015)
The pain of menstruation can cause a nuisance of daily activity. One of the handling way to reduce the level of menstruation pain is doing warm compress. The event rate of menstruation pain in SMAN 2 Pamekasan, 70% female students of tenth grade get the menstruation pain. The research intends to know the relation of warm compress to the level of menstruation pain to female students of tenth grade in SMAN 2 Pamekasan. The design of research is analytic with the construction design of cross sectional, the population is female students of tenth grade who get the menstruation pain on the first until the third day and they don’t take a medicine, which can reduce of the pain. The sample is 88 respondents, sampling simple random sampling. The date that are gotten, are processed with SPSS for windows and are examined by Mann-Whitney with the meaning level α = 0,005. The result of research shows that 88 respondents, the most of 57 respondents who did the warm compress, get the minor of menstruation pain is 31 respondents (54,4%), and 31 respondents who did the usual compress, almost all of them get the minor of menstruation pain, is 25 respondents 76 (80,6%), the test research of Mann-Whitney is gotten p = 0,024 and α = 0,05, it means that ρ < α so H is refused, means that there is correlation between the warm compress to the level of menstruation pain to female students of tenth grade in SMAN 2 Pamekasan. The warm compress reduce the menstruation pain. I hope that the female students handle the menstruation pain by doing warm compress.